The book of disputation: a Mudejar religious-philosophical treatise against Christians and Jews : a study and accompanying text edition - Colominas Aparicio, Mònica (The medieval and early modern Iberian world, 2024)
"This is the first critical edition and study of a unique and important Muslim polemic against Christians and Jews. The Book of Disputation was written in Arabic by a Mudejar (subject Muslim living under Christian rule in late medieval Iberia) and offers new insight into the cultural and intellectual life of this Muslim minority. The text advances arguments drawn from natural philosophy-largely from Aristotle and Averroes-along with more traditional revealed sources such as the Qur'an and the Bible. Mudejar communities suffered a diminution of religious and political intelligentsia over time. This text, however, highlights the author's particular conception of the world as the creation of God in his defense of Islam, demonstrates the vitality of intellectual life among Muslims in medieval Christian Iberia, and documents the continued cultivation of natural philosophy within these Muslim communities"--